Didattica e differenze di genere in alunni di 8-12 anni - Giuseppe Zanniello (LED Edizioni Universitarie, 2013)
Teaching and Gender Differences in 8-12 Year Old Students We present the first results of an extensive study concerning gender differences that are found in school learning. We illustrate them also in order to promote more adequate teaching methods. We analyse nine points of differences between boys and girls in learning and in school behaviour, that should be taken into account in the first cycle of education and that are derived from international studies carried out in Western countries: movement and physical activity within the regular classroom curriculum, cognitive skills, emotions and feelings, relationship with the authority, relationships with peers, metacognitive skills, commitment and perseverance in working, reaction to failure, self-esteem. To assess the results of these studies and to guide teachers firstly in designing and then in reporting their teaching practices that take gender differences into account, we analyse the spontaneous teaching actions of 44 teachers - with students aged between eight and twelve years - who claimed to be attentive to the enhancement of specific feminine and masculine traits in their teaching activities. We identified a total of 24 indicators of gender differences that teachers should consider, partially changing their teaching activities, if they want to give equal opportunities for school achievement to both boys and girls.